The implementation of learning model and virtual lab toward learning outcome of chemistry education - Gulmah Sugiharti; Abdul Hamid; Mukhtar Mukhtar (Pascasarjana Universitas Negeri Medan, 2019)
The abundance of chemical concepts and general chemistry lessons that tend to be monotonous and have not yet considered the ability of mathematical thinking to cause problems in learning that resulted in low student learning outcomes. Even though the concept can be related to students' daily lives by applying effective learning models in accordance with teaching materials. The purpose of this study was to determine whether there were significant differences in learning outcomes between the classes taught with PBL models and the classes taught in the DI model in the General Chemistry course at the Chemistry Education department of FMIPA Unimed. The population consists of 2 classes, each of which consists of 26 students taught with different learning models. After the data is tested normal and homogeneous by using SPSS, the hypothesis is tested using t test. Based on the results of the hypothesis test, it is known that the value of Sig. 0.065 <0.10. So it was said that there were significant differences in learning outcomes of classes taught with PBL models with classes taught with the DI model in General Chemistry courses. This study concludes that for the General Chemistry subject learning, it is better to use the PBL model than the DI model.Keywords: DI model; general chemistry; project-based learning model; virtual lab